Farmers' awareness and factors affecting adoption of rapid composting in Mekong Delta, Vietnam and Central Luzon, Philippines (Journal of Environmental Science and Management, 2012)
A survey of 417 respondents and focus group discussions among selected farmers were conducted in four villages in Mekong Delta, Vietnam and Central Luzon, Philippines. Key informants interviews among representatives of current adoptors of rapid composting, local authorities, agricultural extension offices, cooperatives, farmers' associations, women's groups, and other related institutional organizations in the study sites were also done. The study aimed to: a) determine the current practices of rice straw uses of the farmers in the study sites; b) describe farmers' awareness and perception about using rice straw to produce rapid compost with Trichoderma; and c) determine the factors affecting the acceptance of farmers to do rapid composting.